Traditional medicine among the community of Gash-Barka region, Eritrea: attitude, societal dependence, and pattern of use - Sirak Tesfamariam; Filmon Tesfai; Lemlem Hussien; Yonatan Ateshim; Dawit Yemane; Mulugeta Russom; Hagos Ahmed; Iyassu Bahta; Solyana Ngusbrhan Kidane; Josephine Namboze; Ossy Muganga Julius Kasilo (BMC, 2021)
Abstract Background Despite the growing conventional healthcare coverage in Eritrea, traditional medicine (TM) remains an essential source of healthcare service to the population. This study, therefore, aims at exploring the attitude, societal dependence, and pattern of TM use of the Gash-Barka community. Methods A cross-sectional study was conducted between December 2018 and January 2019 in Gash-Barka region, one of the six regions of Eritrea. Two-stage stratified cluster sampling design was used to provide representative sample of households. The data collected through face-to-face interview using a structured questionnaire was entered twice and analyzed using CSPro7.2 and SPSS 23, respectively. Both descriptive and analytical analyses were performed to test statistical significance. Results Of the total 210 participants, 202 completed the interview with a response rate of 96.2%. Almost 97% of the respondents were aware of the general existence of TM. About half of the respondents (47.4%) had visited traditional health practitioners (THPs) at least once in their lifetime. The majority of the respondents claimed their medical condition had been improved (63.2%), were satisfied with the outcome (76.8%), and had not encountered complications (95.2%) due to TM use. Around 40% of the respondents admitted they do not disclose previous TM use to conventional health practitioners. Females are more likely to have had ever visited THPs (AOR = 1.85, CI: 1.01, 3.38) and use TM in the future (AOR = 2.26, CI: 0.92, 5.14) than males. Moreover, those who had visited THPs before (COR = 8.30, CI: 3.25, 21.20) are more likely to use TM as a primary treatment choice and prefer to use TM in the future (AOR = 4.40, CI: 1.97, 9.83) than those who had never visited THPs. About 61% of the total families claimed they had circumcised at least one female child, and 96.8% disclosed they had circumcised at least one male child. Out of which, 89.2% of the circumcisions were done by THPs. Conclusion TM is popular and widely relayed upon by Gash-Barka residents with exposure of children to harmful TM practices. Since the reliance of the community on TM is expected to continue, further representative studies are recommended to inform regulatory interventions and integrate TM into the health system.